2007
DOI: 10.1002/anie.200700345
|View full text |Cite
|
Sign up to set email alerts
|

A Formally Zwitterionic Ruthenium Catalyst Precursor for the Transfer Hydrogenation of Ketones that Does Not Feature an Ancillary Ligand NH Functionality

Abstract: The ruthenium-mediated transfer hydrogenation (TH) of ketones under basic conditions employing iPrOH or other H 2 -donor solvents has emerged as an atom-economical methodology for the synthesis of secondary alcohols.[1] Although the catalytic abilities of Ru complexes supported by a range of structurally diverse ancillary ligands have been evaluated, precatalysts featuring a RuÀNH linkage commonly offer the highest levels of activity and selectivity in the TH of ketones. [1,2] In the case of the landmark {(h 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
62
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(66 citation statements)
references
References 27 publications
(3 reference statements)
4
62
0
Order By: Relevance
“…8 10 5 h À1 at 50 % conversion) in the presence of 2 (0.005 mol %) and NaOiPr (2 mol %), while the reaction with 3 goes to completion in 5 min (TOF = 1.3 10 6 h À1 ; Table 1). [8] Surprisingly, this rate is slightly higher than that of the analogous compound [RuCl(CNN)(dppb)] (TOF = 1.1 10 6 h À1 ), [6c] which is one of the most active TH catalysts, [9] and, in contrast to the ruthenium-based catalysts, 3 also displays high activity with only one equivalent of NaOiPr (TOF = 1.0 10 6 h À1 ). [10] are the only other systems which allow the TH of ketones at such low catalyst loadings.…”
mentioning
confidence: 96%
“…8 10 5 h À1 at 50 % conversion) in the presence of 2 (0.005 mol %) and NaOiPr (2 mol %), while the reaction with 3 goes to completion in 5 min (TOF = 1.3 10 6 h À1 ; Table 1). [8] Surprisingly, this rate is slightly higher than that of the analogous compound [RuCl(CNN)(dppb)] (TOF = 1.1 10 6 h À1 ), [6c] which is one of the most active TH catalysts, [9] and, in contrast to the ruthenium-based catalysts, 3 also displays high activity with only one equivalent of NaOiPr (TOF = 1.0 10 6 h À1 ). [10] are the only other systems which allow the TH of ketones at such low catalyst loadings.…”
mentioning
confidence: 96%
“…In fact, the formation of 100 has been shown to be a catalyst deactivation pathway in ketone transfer hydrogenation reactions employing 98 or 99 as pre-catalysts. [107] Nonetheless, such an observation does not rule out the involvement of alternative hydrido species as active catalysts in reactions employing 99, including those arising by intramolecular CÀH bond activation, as was observed for 77 (Scheme 22) and 93 (Scheme 26). Whilst in a related investigation little difference was observed between the performance of the cationic and zwitterionic iridium precatalysts 68 and 70 (Figure 4) in the transfer hydrogenation of acetophenone (2 h, 0.1 mol % Ir, 93-98 %; 37 000-47 000 h À1 ), these complexes out-performed Crabtrees catalyst (56, Figure 2), which afforded only 29 % conversion under similar experimental conditions.…”
Section: Carbanion-based Ancillary Ligationmentioning
confidence: 79%
“…[104,105] Divergent catalytic performance was observed in the course of a comparative catalytic investigation to probe the ability of the structurally analogous cationic and zwitterionic (h 6 -arene)Ru complexes 98 and 99 to mediate the transfer hydrogenation of ketones under basic conditions and employing iPrOH as an H 2 donor solvent (Scheme 27). [107] In a preliminary test reaction employing acetophenone (R = Ph in Scheme 27), the cation 98 exhibited only modest activity, with final conversions into 1-phenylethanol in the range of 4-23 %. In stark contrast, the zwitterion 99 afforded 99 % conversion into 1-phenylethanol after only five minutes.…”
Section: Carbanion-based Ancillary Ligationmentioning
confidence: 99%
“…Very recently, Morris group [15,16] reported that chiral NNPP ligands and their iron(II) complexes were effective in the ATH of ketones under mild conditions, representing a rare case of using inexpensive iron as the active metal. Although new ligands and their transition metal complexes have been established in this area [17][18][19][20], the desire for more highly active catalytic systems with better stereoselectivity and broader substrate scopes under mild conditions is still strong. We have recently documented that highly active transition metal complex catalysts could be rationally constructed by introducing a benzimidazolyl or pyrazolyl coordinating arm on a pyridyl-based ligand framework [21][22][23][24][25][26][27][28][29][30].…”
Section: Introductionmentioning
confidence: 99%